2021
DOI: 10.21203/rs.3.rs-282404/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biodegradation α-endosulfan and α-cypermethrin by Acinetobacter schindleri B7 isolated from the microflora of grasshopper (Poecilimon tauricola)

Abstract: Extensive applications of pesticides have led to the contamination of ecosystem. Therefore, the isolation of new pesticide degrading bacteria is important. For the biodegradation of α-endosulfan and α-cypermethrin, new bacteria isolates were isolated from grasshopper (Poecilimon tauricola). According to different tests, these isolated bacteria were identified as Pseudomonas aeruginosa B5, Acinetobacter johnsonii B6, Acinetobacter schindleri B7, Bacillus megaterium B9 and Brevibacillus parabrevis B12. The first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…It is likely that the genera of bacteria for which an increase in abundance was recorded are tolerant to the insecticides used, or maybe they are able to degrade insecticides, making them less effective. The above-mentioned genera of bacteria are known to degrade insecticides (Gilani et al, 2016;Ibrahim et al, 2021;Jaffar et al, 2022;Özdal & Algur, 2020Özdal & Algur, , 2022. For instance, Akami et al (2019) demonstrated that genera including Acinetobacter, Citrobacter, Pseudomonas, Burkholderiales (unclassified genera) are potentially involved in the increased tolerance of their insect host-Callosobruchus maculatus (Coleoptera, Chrysomelidae) against the dichlorvos insecticide (DDVP).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is likely that the genera of bacteria for which an increase in abundance was recorded are tolerant to the insecticides used, or maybe they are able to degrade insecticides, making them less effective. The above-mentioned genera of bacteria are known to degrade insecticides (Gilani et al, 2016;Ibrahim et al, 2021;Jaffar et al, 2022;Özdal & Algur, 2020Özdal & Algur, , 2022. For instance, Akami et al (2019) demonstrated that genera including Acinetobacter, Citrobacter, Pseudomonas, Burkholderiales (unclassified genera) are potentially involved in the increased tolerance of their insect host-Callosobruchus maculatus (Coleoptera, Chrysomelidae) against the dichlorvos insecticide (DDVP).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Burkholderia mallei, Stenotrophomonas maltophilia or Citrobacter amalonaticus can enhance the host's metabolism of insecticides (Wang et al, 2022). Generally, it was noted that the following genera of bacteria: Pseudomonas, Bacillus, Rhodococcus, Stenotrophomonas, Alcaligenes, Serratia and Streptomyces might participate in the degradation of various pesticides (Özdal & Algur, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation